X-ray powder diffraction spectroscopy as a robust tool in early predicting bioavailability of pharmaceutical formulation containing polymorphic drug substance - Mehata A.K.; Dehari D.; Ayyannan S.R.; Muthu M.S. (My University, 2025)
X-ray powder diffraction (XRPD) is a unique, solid-state analytical tool used to study the 3D structure of small or macromolecules by their x-ray diffraction or scattering patterns. X-ray diffraction by a crystal reflects the periodicity of crystal architecture; any imperfections within the crystal architecture can be easily identified by its poor diffraction pattern. Recently, an open crystallography database reported that more than 85 % of drug compounds are crystalline and exist in different polymorphic states. Physicochemical properties of pharmaceutical drug products composed of active pharmaceutical ingredients (APIs) and excipients are interdependent on the physical state and forms in which APIs are distributed in excipients that determine the in-vivo and ex-vivo performance of the product. Amorphous APIs have relatively higher dissolution and bioavailability than crystalline form but with lower phase stability. During the formulation development and storage phase, the conversion is higher that largely impacts the bioavailability of the drug product. In this manuscript, we have presented the case study of itraconazole and apigenin; both are crystalline APIs, that, with the help of solid dispersion technology, are converted into amorphous drug products with enhanced oral bioavailability. The realtime monitoring of the physical form of API in the formulation was possible with the help of XRPD and other supporting data obtained from differential scanning calorimeter (DSC), which can be correlated with the dissolution and in-vivo performance of the formulation. © 2020 Bentham Science Publishers.